KEBIJAKAN HUKUM PIDANA TERHADAP KEJAHATAN PEMERASAN SEKSUAL ( SEKSTORSI ) DI INDONESIA - Wulan Novita Sipayung; Erdianto Erdianto; Syaifullah Yophi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
The crime of sexual extortion/sextortion is a form of online gender-based violence that is carried out by extorting the victim both materially and sexually by utilizing pornographic photos or videos belonging to the victim which are obtained either by hacking, or given directly by the victim on the basis of trust in a relationship. Therefore, the purpose of this thesis research is, firstly, the importance of legal arrangements for crimes of sexual extortion/sextortion in Indonesia. Second, how is the legal protection of women as victims of sexual extortion/sectoral crimes in Indonesia.This type of research uses normative legal research methods, namely research that uses laws and regulations as primary legal material. The data sources used are primary data, secondary data, tertiary data, the data collection technique in this study is normative juridical, the data used is library research.From the results of the research problem there are 2 main things that can be concluded. First, the regulations relating to the crime of sexual extortion/sextortion are currently not very clear and complete, so that the handling of sextortion cases is not yet able to provide appropriate legal protection for victims of sextortion. The two positive laws in Indonesia relating to sextortion crimes currently only regulate prohibitions and sanctions against the perpetrators, but there is no perspective on the victim. The author's suggestion is First, there is a need for a policy to reform the criminal law that regulates sexual extortion crimes. Second, there is a need for more complete and clear rules regarding sextortion crimes. Keywords: Sextortion, Protection, Victim